KILKA UWAG O BADANIACH NAD ROMANIZACJĄ STATUTÓW LITEWSKICH - Godek, Sławomir (Zeszyty Prawnicze, 2017)
SOME REMARKS ON THE STUDY OF THE ROMANIZATION OF LITHUANIAN STATUTES Summary The article is dedicated to the issues connected with the reception of Roman Law in the Lithuanian statutes of 1529, 1566, and 1588. After an analysis of the existing scholarly accomplishments in the field, one cannot but conclude that the study of the influence of the Roman Law on Lithuanian codifications has hardly been started yet. Despite the fairly long tradition of research in this field, so far only selected elements of the first and second statutes have been analyzed in order to identify Roman constituents. The research carried out in 1930s by Raphael Taubenschlag, Franciszek Bossowski, and Karol Koranyi demonstrated which Roman Law noticeably influenced the statutory regulations pertaining to family law, law of property, law of succession, criminal and procedural law. Their observations partly confirmed the findings previously made in the nineteenth century by Aleksander Mickiewicz, Franciszek Morze, and Ignacy Daniłowicz. At the same time, nothing is still known about the scope of Romanization in the third Lithuanian statute or about the transformations which Roman elements underwent in each of the statutes. Without further study of the subject, one cannot assess the role of Roman law in the Commonwealth (Rzeczpospolita). It seems that the most fertile ground for identification of Roman elements in the third Lithuanian statute is tutorship and succession law, especially testamentary succession. Some interesting and original observations could be made on the basis of a more thorough comparative analysis of the pertinent Roman and Lithuanian regulations.